Canine periosteal osteosarcoma - Gabriela Noronha, T. [UNESP]; Julio Edward, H. M. [UNESP]; Costa, Rodrigo Casarin [UNESP]; Rosemeri Oliveira, V. [UNESP]; Mirela Tinucci, C. [UNESP]; Andrigo Barboza, N. [UNESP] (Universidad de Cordoba, 2018)
Osteosarcoma is the most common bone tumor in dogs. The periosteal osteosarcoma is a subtype of osteosarcoma, and is considered rare in the canine species. The purpose of the present study was to describe a 14-year-old female dog with an ulcerated mass located in the right tibia and 30-days of evolution. The patient was submitted to complementary exams (blood count analysis, dosage of biochemical enzymes - creatinine and alanine aminotransferase, thoracic radiographs, and abdominal ultrasonography) to perform complete staging of the disease. Radiography of the right tibia revealed proliferative and lytic periosteal reaction. The cytological analysis of the mass suggested a round cell tumor. The clinical and the radiological findings indicated the presence of a bone tumor. Pelvic limb amputation was the initial surgical treatment suggested to the client. The histopathological examination revealed the presence of periosteal osteosarcoma with free margins and lymph nodes without evidence of tumor cells. Clinical follow-up was performed through imaging exams without evidence of metastatic disease. The dog had a nine-month survival free time from diagnosis.

El osteosarcoma es el tumor óseo más común en los perros. Osteosarcoma periosteal es un subtipo de osteosarcoma y se considera raro en la especie canina. El objetivo del presente estudio fue describir un caso de una perra mestiza de 14 años de edad con una masa ulcerada y localizada en la tibia derecha y 30 días de evolución. él paciente se sometió a exámenes adicionales (análisis de sangre, dosis de enzimas bioquímicas - creatinina y alanina aminotransferasa, radiografías torácicas y ultrasonografía abdominal) para la estadificacion completa de la enfermedad. La radiografía de la tibia derecha reveló reacción perióstica proliferativa y lítica. él examen citológico de la masa sugirió un tumor de celulas redondas. La evaluación clínica y hallazgos radiológicos sugieren la presencia de una neoplasia ósea. La amputación de la extremidad pélvica derecha fue el tratamiento quirúrgico inicial sugerido al cliente. él examen histopatológico reveló la presencia de osteosarcoma periosteal con márgenes libres y ganglios linfáticos sin evidencia de células tumorales. El seguimiento clínico se realizó a través de exámenes de imágenes sin evidencia de enfermedad metastásica. El perra tenía un tiempo de sobrevida de nueve meses desde el diagnóstico.
Osteosarcoma periosteal en perro
Keywords: Bone tumor; Dog; Neoplasia; Periosteum; Veterinary pathology (Source: MeSH)